Fascin expression in cholesteatoma: correlation with destruction of the ossicular chain and extent of disease - BATMAN, ABDULLAH ÇAĞLAR; YUMUŞAKHUYLU, ALİ CEMAL (WILEY-BLACKWELL, 2015)
ObjectiveFascin is an actin-bundling protein found in cell membrane protrusions and increases cell motility. The expression of fascin in epithelial neoplasms has been described only recently. No data are available concerning the role of this protein in invasive cholesteatoma. Thus, we investigated the expression of fascin in cholesteatoma tissue and the relationship between fascin expression and intraoperative evaluation of the destruction of the ossicular chain and extent of disease. MethodCholesteatoma specimens of 28 patients and external auditory canal (EAC) skin specimens of the same patients (as the control group) were collected from mastoidectomies. Immunohistochemical technique was used to investigate the fascin expression in all cholesteatoma tissues and EAC skin specimens. Immunohistochemical staining was assessed semiquantitatively based on the thickness of epithelium. SPSS software version 16.0 (SPSS Inc., Chicago, IL, USA) was performed to statistically analyse the relationships between fascin expression and intraoperative evaluation destruction of ossicular chain and extent of the disease. ResultsImmunohistochemically, there was no or very low fascin expression observed in normal epithelial cells of EAC skin, while expressed in cholesteatoma tissue. Also, fascin expression in cholesteatoma tissues was significantly correlated with destruction of ossicular chain and extent of the disease. ConclusionsFascin expression is usually found in cholesteatoma epithelium and is correlated with destruction of the ossicular chain and extent of disease. Considering all of the correlations between the clinical and histopathological findings, fascin immunoexpression scoring' may be used for histological grading of cholesteatoma.
Keywords: SQUAMOUS-CELL CARCINOMA; ACTIN CYTOSKELETON; MOTILITY; CORTACTIN; BIOMARKER; EVENTS; CANCER; ROLES